Solid Phase Extraction of Trace Amounts Cu, Fe and Pb as 5-(6-Methoxy-2-benzothiazoleazo)-8-aminoquinoline Complexes on Naphthalene Adsorbent and Flame Atomic Absorption Determination - JAVAD POURSHARIFI., MOHAMAD; MOGHIMI, ALI (Asian Journal of Chemistry, 2010)
A simultaneous preconcentration method was developed for the determination of trace amounts of Cu, Fe and Pb by atomic absorption spectrometry. The method is based on the retention of their 5-(6-methoxy- 2-benzothiazoleazo)-8-aminoquinoline complexes by naphthalene methyltrioctyl ammonium chloride adsorbent in a column. The adsorbed metal complexes were eluted from the column with nitric acid and Cu, Fe and Pb were determined by flame atomic absorption spectrometry. Several parameters such as pH of the sample solution, ligand concentration, volume of the sample and the amount of methyltrioctyl ammonium chloride loaded on naphthalene were evaluated. The effect of diverse ions on the preconcentration was also investigated. A preconcentration factor of up to 100 or more can easily be achieved depending on the volume of the sample taken. The calibration graphs were obtained in the range of 5-40, 10-100 and 10-200 ng mL-1 for Cu, Fe and Pb in the initial solution, respectively, when using 500 mL of the solution. The detection limit based on three standard deviations of the blank was 0.54, 3.1 and 4.5 ng mL-1 for Cu, Fe and Pb, respectively. The relative standard deviations of 1.1-2.4 % for Cu, 2.0-3.1 % for Fe and 1.1-2.0 % for Pb were obtained. The method was applied to the determination of Cu, Fe and Pb in river and wastewater samples.